UI/UX Analysis of Project Management Information System (PMIS) Website Using User-Centered Design Method - Azhar, Sarah Afifah; Defriani, Meriska; Hermanto, Teguh Iman (Sinkron : jurnal dan penelitian teknik informatika, 2023)
In Industry 4.0, a lot of data has been digitized and is no longer stored manually. In helping to record all the projects that were worked on initially stored in outstanding Project Management applications such as Trello. However, the Trello application has limitations and compatibility with business processes, including employees not writing down projects that have been done because they are not in accordance with procedures, causing many projects to go unrecorded. So because of these limitations a Project Management Information System (PMIS) website is needed which makes it easy to record all projects so that there is no more unrecorded data. Furthermore, there are problems in conducting an analysis that can make it easier for users and how to design a User Interface and User Experience on the PMIS website using the User Centered Design (UCD) method, which in the manufacturing process will continue to make changes according to needs. The results of the User Interface design that has been made will be tested for User Experience using the Single Ease Questionnaire (SEQ) method as a measure of the success of the User Interface that has been made. Based on the results of the User Experience test using the Single Ease Questionnaire method for 5 respondents, an average value of 6.3 was obtained, which means that it can be concluded that the User Interface that has been created has a level of convenience that is in accordance with the User Experience.